Longitudinal Cognitive Trajectories of Women Veterans from the Women's Health Initiative Memory Study. (27th November 2015) - Padula, Claudia B.; Weitlauf, Julie C.; Rosen, Allyson C.; Reiber, Gayle; Cochrane, Barbara B.; Naughton, Michelle J.; Li, Wenjun; Rissling, Michelle; Yaffe, Kristine; Hunt, Julie R.; Stefanick, Marcia L.; Goldstein, Mary K.; et al.
Abstract: Purpose of the Study: A comparison of longitudinal global cognitive functioning in women Veteran and non-Veteran participants in the Women's Health Initiative (WHI). Design and Methods: We studied 7, 330 women aged 65–79 at baseline who participated in the WHI Hormone Therapy Trial and its ancillary Memory Study (WHIMS). Global cognitive functioning (Modified Mini-Mental State Examination [3MSE]) in Veterans ( n = 279) and non-Veterans ( n = 7, 051) was compared at baseline and annually for 8 years using generalized linear modeling methods. Results: Compared with non-Veterans, Veteran women were older, more likely to be Caucasian, unmarried, and had higher rates of educational and occupational attainment. Results of unadjusted baseline analyses suggest 3MSE scores were similar between groups. Longitudinal analyses, adjusted for age, education, ethnicity, and WHI trial assignment revealed differences in the rate of cognitive decline between groups over time, such that scores decreased more in Veterans relative to non-Veterans. This relative difference was more pronounced among Veterans who were older, had higher educational/occupational attainment and greater baseline prevalence of cardiovascular risk factors (e.g., smoking) and cardiovascular disease (e.g., angina, stroke). Implications: Veteran status was associated with higher prevalence of protective factors that may have helped initially preserve cognitive functioning. However, findings ultimately revealed more pronounced cognitive decline among Veteran relative to non-Veteran participants, likely suggesting the presence of risks that may impact neuropathology and the effects of which were initially masked by Veterans' greater cognitive reserve.